2022
DOI: 10.1002/aenm.202103652
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Mechanism of Poly(ionic‐liquid)s Multiple Inhibition of Ion Migration for Efficient and Stable Perovskite Solar Cells

Abstract: make it one of the most promising photovoltaic technologies. [1,2] Although such solar cells have been demonstrated with a certified power conversion efficiency (PCE) reaching 25.5% for laboratory scale devices, [3] successful commercialization of PVSCs still lacks mature large-area manufacturing technology and reliable long-term stability. [4] With the continuous improvement of printing technology, the fabrication of large-area perovskite photovoltaic devices has become possible and is expected to be compatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 62 publications
(63 reference statements)
1
50
0
Order By: Relevance
“…We can find that the migration distances are extended for both R-α-MBA- and R-α-BrMBA-incorporated cases. 67 Furthermore, the calculated migration energy for R-α-MBA- and R-α-BrMBA-incorporated cases are around two-fold higher than that of the control. 68 The substantially higher migration energy indicates that I − ion migration in the 2D/3D layers is suppressed significantly, which may be due to the steric impediment effect from larger spacer cations.…”
Section: Resultsmentioning
confidence: 95%
“…We can find that the migration distances are extended for both R-α-MBA- and R-α-BrMBA-incorporated cases. 67 Furthermore, the calculated migration energy for R-α-MBA- and R-α-BrMBA-incorporated cases are around two-fold higher than that of the control. 68 The substantially higher migration energy indicates that I − ion migration in the 2D/3D layers is suppressed significantly, which may be due to the steric impediment effect from larger spacer cations.…”
Section: Resultsmentioning
confidence: 95%
“…[71,77] Moreover, the functionalized ILs with imidazolium group or quaternary ammonium groups, which are enabled with the ability to form hydrogen bonds with the I À , Br À , and Cl À in perovskite materials, effective anchoring the I À , Br À , and Cl À for inhibition of instability caused by ion migration. [78] The formation of O⋯H-N hydrogen bonds between the carboxyl and ester groups in ILs with MA þ or FA þ also leads to the stabilization of organic ions. [79] The photovoltaic parameters of stable ILs-treated PSCs through chemical interaction are summarized in Table 3.…”
Section: Chemistry Interactionmentioning
confidence: 99%
“…As a result, the PEa poly‐RTMS‐treated PSCs displayed a high PCE of 21.4% and a long‐term operational stability that remained more than 92% of its initial efficiency after 1200 h at 70−75 °C. Taking the advantage of formation of chemical interaction in the multiple repeating units, the PILs [poly‐1,3‐ bis (4‐ethylbenzyl)‐imidazolium chloride (PIL‐[bebim]Cl)], [ 54 ] [poly‐1‐vinyl benzyl‐triethylammonium chloride (PIL‐Am)], and [poly‐1‐vinyl benzyl‐3‐methylimidazole chloride (PIL‐Im)] [ 78 ] have been also employed to improve device stability. These PILs that combine the advantage of polymers and ILs include the structural designability, excellent chemical durability and thermal stability, which adds to the polymerizable ILs or PILs the potential of prolonging the service life of the device.…”
Section: Strategies For Improving Of the Stability Of Pscs By Ilsmentioning
confidence: 99%
“…27 In perovskite optoelectronic devices, ILs have been shown to passivate defects, 28 improve stability, 29 and replace traditional solvents to control crystal growth kinetics. 30 Although ILs have been widely employed to enhance the performance of perovskite solar cells (PSCs), 31 their application in PeLEDs is barely reported. 32,33 Here, we demonstrated that the use of quaternary ammonium salt-based ILs as the interfacial modification layer can greatly improve the efficiency and stability of the blue PeLEDs.…”
Section: Introductionmentioning
confidence: 99%